Characterization and Quantification of Municipal Solid Waste in Jeetpur Simara Sub- Metropolitan City, Nepal - Dahal, Yubraj; Adhikari, Bikash (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Waste management, being one of the most important aspects of urban development, is gaining importance among developing nation like Nepal where rapid population growth, unmanaged urbanization, lack of public awareness and poor management by municipalities have intensified environmental problems in towns in Nepal. In Nepal only six municipalities i.e. Kathmandu, Lalitpur, Pokhara, Dhankuta, Tansen and Ghorahi practice sanitary landfill for waste management and other municipality practices open dumping which has become major cause of environmental and human health hazards (ADB, 2013). Jeetpur Simara Sub-Metropolitan City (JSSMC) is a recently formed sub-metropolitan city. This city has not performed any study on solid waste management till date and lacks data on quantity and composition of municipal solid waste generation that facilitates effective planning of municipal solid waste management. The household survey revealed an average per capita household waste generation rate of 120 g/capita/day. The total Municipal Solid Waste (MSW) generation is estimated about 15 tons/day and 5475 tons/year. The analysis of household waste composition indicated that the highest waste category was organic waste with 80% followed by plastics with 10%, paper and paper products with 6% and inert with 4%. The composition analysis of institutional wastes revealed 41% paper and paper products, 33% plastics, 13% organic wastes and 13% inert. The study found that commercial waste comprised 59% paper and paper products, 21% plastics, 17% organic and 3% inert. In aggregate, MSW is composed of 56% organic waste, 21% paper and paper products, 19% plastics, and 3% inert. HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 45-47 Uploaded date: January 14, 2018